A newly developed continuous zoom-focus endocytoscope - Kumagai, Youichi; Takubo, Kaiyo; Kawada, Kenro; Higashi, Morihiro; Ishiguro, Toru; Sobajima, Jun; Fukuchi, Minoru; Ishibashi, Kei-ichiro; Mochiki, Erito; Aida, Junko; Kawano, Tatsuyuki; Ishida, Hideyuki (Endoscopy, 2017)
Background and study aims We report the features of a newly developed endocytoscopy system (ECS), the GIF-Y0074.Patients and methods The GIF-Y0074 offers high-definition resolution with a consecutive increase of magnification to × 500. Using ECS, we observed 32 cases of esophageal squamous cell carcinoma (ESCC), 11 cases of gastric cancer, and five cases of duodenal adenoma.Results The images of cells obtained using the GIF-Y0074 at maximum magnification were brighter and clearer than those obtained with previous ECS systems. For diagnosis of ESCC, clearer visualization of the nucleus made nuclear abnormality easier to recognize. Cancer cells were visualized in 10/11 cases of gastric cancer, but removal of mucus still remained a problem. Duodenal adenomas were found to have atypical cells with villi and tubules at the mucosal surface, thus assisting their histological diagnosis in vivo. Conclusion The GIF-Y0074 is an excellent ECS in terms of ease of use, satisfactory resolution, and magnification power, and therefore achieves a level of utility that makes its commercial release justifiable. This ECS heralds a new era of endoscopic and histological diagnosis.